A multilevel study of transformational leadership, dual organizational change and innovative behavior in groups. Issue 6 (3rd October 2016) - Feng, Cailing; Huang, Xiaoyu; Zhang, Lihua
Abstract : Purpose: Based on dual organizational theory, the purpose of this paper is to examine the relationship between transformational leadership and innovative behavior in groups. The authors proposed that group innovative behavior was influenced by transformational leadership as a group-level construct which was moderated by dual organizational change that represent organization-level resources. Furthermore, the authors identified two organizational change-related situational variables-radical change and incremental change and examined their effects on group innovative behavior. Design/methodology/approach: The authors collected data from full-time employees working in groups in 43 companies, located in five cities in China including Beijing, Yantai, Chengdu, Xi'an, and Chengde. These enterprises were from a wide range of industries, including manufacturing, financing, information technology, and geological exploration. The authors chose a middle- or senior-level manager from each company to act as chief survey respondent, who were asked to contact managers and employees from a list they had provided and invite them to participate in a web-based survey (via an e-mailed link) or a paper-and-pencil survey. A total of 192 managers and 756 direct subordinates from 112 groups completed the survey. Findings: Results found that transformational leadership was positively related to group innovative behavior, and this relationship was moderated by radical change, but not incremental change; radical change and incremental change were also positively related to group innovative behavior. Research limitations/implications: This study adopts a cross-sectional study design, which is insufficient for deriving causal inferences. Future research may adopt a longitudinal study design to investigate causal impacts. Besides, some unmeasured variables could be related to transformational leadership and innovative behavior. Practical implications: The paper includes implications for adopting appropriate leadership style to motivate innovative behavior, promoting dual organizational change to boost innovative behavior, and generating greater innovative behavior for transformational leaders in times of radical change. Originality/value: This cross-level study contributes to the relationship between transformational leadership and group innovative behavior in the context of dual organizational change.